Big fish - Burton, Tim, 1958-; McGregor, Ewan, 1971-; Finney, Albert, 1936-; Crudup, Billy, 1968-; Wallace, Daniel, 1959- (Culver City, Calif. : Columbia TriStar Home Entertainment, 2004)
As his father Edward lies on his deathbed, William Bloom attempts to get to know him beyond the tall tales he tells about his life, and learns to understand and accept him along the way.
Based on the novel by Daniel Wallace.
Features: Tim Burton Audio commentary -- Character's journey -- Edward Bloom at large -- Amos at the circus -- Fathers and Sons --The filmmakers path -- Tim Burton Storyteller -- A fairytale world -- Crature features --The author's journey --deleted scenes, featurettes, scene selection, trailers, trivia quiz.
Ewan McGregor, Albert Finney, Billy Crudup, Jessica Lange.
MPAA rating: PG-13.
DVD, Dolby digital 5.1 surround.
In English or French with optional English or French subtitles ; closed-captioned.
Keywords: Fathers and sons -- Drama; Video recordings for the hearing impaired; Feature films; Fantasy films